A review on caring of surgical wound after surgical procedure - Singh, Mahendra; Kumar, Dheeraj (International Journal of Research in Medical Sciences, 2023)
Inadequate wound healing and scar formation continues to be major issues in day-to-day surgical practice. A wound infection (like pus formation, smelly discharge, and the incision line’s opening etc.) is one of them complications of surgical procedure. An infection may appear in surgical wound due to lack of care in post-operatively like dressing not being changed after regular interval, not following aseptic protocol during the dressing, and the dressing material not properly sterilized. Hence, the aim of proper care in post-operative practice was to reduce the risk of infection in surgical wound and promote healing. One of the most important aspects of post-operative wound care is prompt wound evaluation, appropriate hand washing, adhering to aseptic protocol when dressing, using sterile dressing material each time, and proper cleaning of the wound, as well as the prompt identification and management of wound complications.